The Influence of Audit Quality, Public Accounting Firm Size and Tax Planning on Earnings Management - Fahreza Gadjali Rahim; Sony Devano; Ahmad Zakie Mubarrok (Dinasti Publisher, 2025)
This research aims to examine the influence of Audit Quality, Accounting Firm Size, Tax Planning on Profit Management. This quantitative research uses the transportation services sub-sector. Secondary research data was taken from companies listed on the Indonesia Stock Exchange for the 2018-2023 period using a purposive sampling technique. The influence of audit quality uses two measurement indicators, namely audit fees and audit industry specialization, for measuring KAP size using the number of auditors, then for measuring Tax Planning using Book Tax Difference and for measuring Profit Management using Discretionary Accrual. The analysis techniques used in this research are descriptive statistical analysis, classical assumption testing and Multiple Linear Regression to test the influence of audit quality, Accounting Firm Size, tax planning on earnings management. The research results show that audit quality with the audit fee indicator has no effect on earnings management, audit quality with the industry specialization indicator has a significant negative effect, Accounting Firm Size has a significant negative effect on earnings management, tax planning has no effect on earnings management and audit quality, Acounting Firm Size, Tax Planning influence earnings management.